Strategic Planning of Correspondence Service Information System using TOGAF ADM Framework - Putri, Novianti Indah; Yogi Saputra; Zen Munawar; Nurhayati Mahmud (CV. Generasi Intelektual Digital, 2024)
Rapid advancements in information technology have led to businesses and government organizations implementing information systems to improve corporate operations. One of the services provided by the village is correspondence, which includes creating letters of recommendation for application letters. In Leubatang Village, correspondence services are still conducted by hand, and data is gathered using physical books, which makes it difficult to locate data and leaves it susceptible to This study uses the TOGAF ADM framework to suggest strategic planning for Leubatang Village's communication information system. Architectural strategies, gap analyses, business architecture analyses, and technological needs analyses are all prepared using PEST analysis. This strategy planning can be implemented in two to three years, according to the blueprint. Leubatang Village’s correspondence services can be developed using the information system architecture’s design as a foundation for implementation and as a guide.